(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Artificial Intelligence can represent a valuable resource in managing migration flows. AI algorithms can perform several tasks including border controls, identity checks and predictive policing procedures. However, the utilization of such tools in the migration context raises several issues which must be analyzed and discussed in their implications. The presence of bias in datasets can lead to outcomes detrimental to the already vulnerable conditions of migrants. Furthermore, the inherent opaqueness of AI algorithms working routine does not allow the formulation of a clear accountability framework. This article aims to address these concerns to formulate valid answers from a legal and technological perspective, mainly focusing on the European Union approach to these issues.AI-driven migration management procedures: fundamental rights issues and regulatory answers